Strategi Penguatan Ekonomi Kreatif Desa Wisata Melalui Program Akademi Desa Wisata (DEMI DEWI) Tahun 2024: Studi Kasus Wisata Tumpak Selo Desa Petahunan - Fatlurrahman, Fatlurrahman; Maghfira, Sabrina Rahmadhanty (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
Tourism villages play an important role in promoting local economic development. However, many still face challenges in managing tourism potential and developing creative economy activities in a sustainable manner. The DEMI DEWI Program 2024 initiated by the Provincial Government of East Java, aims to strengthen the capacity of Village-Owned Enterprises (BUMDes) and tourism villages in managing local potential creatively and innovatively. This study aims to analyze strategies for strengthening the creative economy and the forms of stakeholer collaboration in implementing the DEMI DEWI Program in Tumpak Selo Tourism Village, Lumajang Regency. This research employs a qualitative descriptive approach, with data collected through observation, semi-structured interviews, and documentation. The results indicate that the program contributes to improving human resource capacity, strengthening destination branding, and promoting cross-sector collaboration among government, academia, business actors, and local communities. These findings highlight the importance of collaborative governance in strengthening the creative economy and supporting the development of independent, innovative, and sustainably competitive tourism villages. Keywords: tourism village, creative economy, community empowerment; collaborative governance